The ABC Concept—Value Added to the Earth Heritage Interpretation? - Pásková, Martina. (2021)
Holistic interpretation of Earth heritage is one of the most important tasks of UNESCO Global geoparks. The ABC (abiotic, biotic, and cultural interconnections) concept is a potential interpretive approach used in Earth heritage popularization through geotourism. Apart of the deeper understanding of this concept, this study explores the application of this concept in selected geoparks. The Colca and Volcanoes Andagua UNESCO Global Geopark (Peru) and Muroto UNESCO Global Geopark (Japan) served as a case study in the frame of this qualitative research conducted during the summer 2019. Results show that the ABC approach is nearly perfectly understood by both geoparks, however there are both internal and external factors which influence the extent and form of how this concept is applied in practice. Except for specific geographical settings, different stages of geopark product development, and different managerial approaches, they mainly include the level of scientific knowledge and general education in the given geopark, as well as level of knowledge management and networking with another UNESCO global geoparks. The more experienced Muroto Geopark interpretation exhibits a comparatively higher level of visible ABC application, while the Colca and Volcanoes Andagua Geopark can benefit in the future from the natural inclination and ability of the local people to integrate the cultural aspects into their Earth heritage interpretation.